Metabolic Acidosis Is an Independent Risk Factor of Renal Progression in Korean Chronic Kidney Disease Patients: The KNOW-CKD Study Results - Kim, Hyo Jin; Ryu, Hyunjin; Kang, Eunjeong; Kang, Minjung; Han, Miyeun; Song, Sang Heon; Lee, Joongyub; Jung, Ji Yong; Lee, Kyu-Beck; Sung, Suah; Seong, Eun Young; Ahn, Curie; et al. (Frontiers in Medicine, 2021)
Background: We aimed to evaluate serum bicarbonate as a risk factor for renal progression, cardiovascular events, and mortality in Korean CKD patients. Methods: We analyzed 1,808 participants from a Korean CKD cohort whose serum bicarbonate levels were measured at enrollment. Serum bicarbonate levels were categorized as low, lower normal, higher normal, and high (total carbon dioxide <22, 22–26, 26.1–29.9, and ≥30 mmol/L, respectively) groups. Metabolic acidosis was defined as a serum bicarbonate level <22 mmol/L. The primary outcome was renal events defined as doubling of serum creatinine, 50% reduction of eGFR from the baseline values, or development of end-stage kidney disease. The secondary outcome consisted of cardiovascular events and death. In addition, patients whose eGFR values were measured more than three times during the follow-up period were analyzed for eGFR decline. The rapid decline in eGFR was defined as lower than the median value of the eGFR slope. Results: The mean serum bicarbonate level was 25.7 ± 3.7 mmol/L and 240 (13.2%) patients had metabolic acidosis. During the follow-up period of 55.2 ± 24.1 months, 545 (30.9%) patients developed renal events and 187 (10.6%) patients developed a composite of cardiovascular events and death. After adjustment, the low serum bicarbonate group experienced 1.27 times more renal events than the lower normal bicarbonate group [hazard ratio (HR): 1.27; 95% CI: 1.01–1.60, P = 0.043]. There was no significant association between the bicarbonate groups and the composite outcome of cardiovascular events and death. The low bicarbonate group showed a significantly rapid decline in eGFR [odds ratio (OR): 2.12; 95% CI: 1.39–3.22, P < 0.001] compared to the lower normal bicarbonate group. Conclusions: Metabolic acidosis was significantly associated with increased renal events and a rapid decline in renal function in Korean predialysis CKD patients.